Critical appraisal of neuropathic pain guidelines in Asia - Rizaldy Taslim Pinzon; Rosa De Lima Renita Sanyasi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Neuropathic pain (NP) is type of chronic pain that is common and often difficult to treat. Clinicians may be guided by a number of published guidelines and algorithms for the management of neuropathic pain. It is important for every clinician to know the quality of guidelines. The availability of current guideline in Asian countries is not well understood. Critical appraisal of NP guidelines in Asia has not performed, yet. The aim of this study was to appraise the quality of pharmacological treatment from neuropathic pain guidelines in Asia. Systematic searches were conducted by using combination of keywords i.e NP, Asia, and guideline. Guidelines evaluation was using appraisal of guidelines for research & evaluation II (AGREE II) instrument. The result interpreted as (i) a strongly recommended for use in practice if most domains scored above 50%; (ii) recommended for use with some modification if most domains scored between 30% to 50%; or (iii) not recommended for use in practice if most domains scored below 30%. After matched to inclusion and exclusion criteria there were 5 guidelines left: a guideline from Philippines, China, South Korea, Malaysia and Middle East. All of guidelines are recommended for use with some modification. The guidelines mention that first line treatment for NP are tricyclic antidepressants, selective norepinephrine reuptake inhibitor (SNRI) and alpha 2-delta ligand calcium channel blocker (CCB). Most of the evidences come from peripheral NP. There were limited evidences for the treatment of central neuropathic pain (central post stroke pain and pain after spinal cord injury). All the existing guideline mention, that the first line treatment for neuropathic are the tricyclic antidepressants, SNRI and alpha 2-delta ligand CCB.